The contributions of deleterious rare alleles in NLRP12 and inflammasome-related genes to polymyalgia rheumatica - Takashi Higuchi; Shomi Oka; Hiroshi Furukawa; Shigeto Tohma (Scientific Reports, 2024)
Abstract Polymyalgia rheumatica (PMR) is a chronic inflammatory disease characterized by arthralgia and myalgia of the shoulder and hip girdles, and fever. PMR is linked to autoimmune diseases and autoinflammatory disorders. Exome sequencing has revealed the roles of rare variants in some diseases. Causative genes for monogenic autoinflammatory disorders might be candidate genes for the selective exome analysis of PMR. We investigated rare variants in the coding and boundary regions of candidate genes for PMR. Exome sequencing was performed to analyze deleterious rare variants in candidate genes, and the frequencies of the deleterious rare alleles in PMR were compared with those of Japanese population controls. Deleterious rare alleles in the NLRL12 gene were associated with PMR (P = 0.0069, Pc = 0.0415, odds ratio [OR] 4.49, 95% confidence interval [CI] 1.79–11.27). A multigene analysis demonstrated the deleterious rare allele frequency of the candidate genes for autoinflammatory disorders was also increased in PMR (P = 0.0016, OR 3.69, 95%CI 1.81–7.54). The deleterious rare allele frequencies of the candidate genes including NLRP12 were increased in PMR patients, showing links to autoinflammatory disorders in the pathogenesis of PMR.